(untitled) - Regis, Edward (Boston, 1995)
It's the ultimate technology: nanotechnology--the attempt to build ordinary objects from the atoms up, molecule by molecule. So named because its building blocks are the smallest pieces of matter, nanotechnology will give us complete control over the structure of matter, allowing us to build any substance or structure permitted by the Laws of Nature. Placing atoms as if they were bricks, nano-machines could turn grass clippings into prime sirloin--directly, without cows.
Keywords: Nanotechnology,Công nghệ nano